Method for measuring rice grain internal damage degree undergoing threshing force - Ren, Hui; Tang, Zhong; Li, Xiyao; Li, Yu; Liu, Xin; Zhang, Biao; Li, Yaoming (International Journal of Agricultural and Biological Engineering, 2021)
During the threshing process of rice, the grains fall off the head of the rice ear due to the impact of the threshing bar. At the same time, the impact force of the threshing element causes a certain degree of damage to the grain. However, there are relatively few methods to analyze the internal damage of rice grains during the threshing process. In this study, the connection force between rice grains and stalks and the compressive bearing capacity of the grains were tested on a push-pull test machine, and then the critical impact force and velocity of rice grains during plastic deformation and brittle fracture were obtained by Hertz theory. On this basis, the quantitative evaluation model of grain internal damage was established through the extraction and calculation of the damaged area inside the grain, and the damage degrees inside the grain under different loading times and loading forces were analyzed. The results showed that the average threshing force required for rice grains is 1.57 N (variance is 0.0529), and the critical impact forces for plastic deformation and brittle fracture of the grains during threshing are 138.79 N and 145.77 N. Since the threshing force during the threshing process was 43.9-71.9 N, it could be known from the internal damage model that the grain is in the safe loading area. Under the same load, the vertical pressure causes the most damage, the lateral pressure takes second place, and the positive pressure was the least. The results of this study can provide a basis for the development of combine harvester and rice grains damage evaluation.Keywords: threshing process, internal damage of grain, threshing force of roller, plastic deformation, critical impact forceDOI: 10.25165/j.ijabe.20211401.5750Citation: Ren H, Tang Z, Li X Y, Li Y, Liu X, Zhang B, Li Y M. Method for measuring rice grain internal damage degree undergoing threshing force. Int J Agric & Biol Eng, 2021; 14(1): 63–73.